Síndrome de Eisenmenger na gravidez - Borges, Vera Therezinha Medeiros [UNESP]; Magalhães, Claudia Garcia [UNESP]; Martins, Anice Maria V. C. [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (FapUNIFESP (SciELO), 2008)
Eisenmenger's syndrome consists of pulmonary hypertension with a reversed or bidirectional shunt at the atrioventricular, or aortopulmonary level. Eisenmerger's syndrome in pregnancy is usually associated with high mortality rates (nearly 30-50%). Unfortunately, pulmonary hypertension is aggravated during pregnancy and often leads to an unfavorable outcome. Here, we report a successful pregnancy in a woman with Eisenmenger syndrome.
Eisenmenger syndrome in pregnancy
Keywords: Hypertension, pulmonary; Pregnancy; acetylsalicylic acid; budesonide; cefalotin; corticosteroid; diuretic agent; formoterol; heparin; oxygen; adult; anamnesis; asthma; bronchitis; case report; cesarean section; clinical feature; Doppler echography; edema; Eisenmenger complex; female; fetus lung maturity; heart transplantation; human; lung transplantation; maternal hypertension; oxygen therapy; phlebotomy; physical examination; pulmonary hypertension; two dimensional echocardiography; Adult; Anticoagulants; Cesarean Section; Eisenmenger Complex; Female; Humans; Hypertension, Pulmonary; Infant, Newborn; Oxygen Inhalation Therapy; Pregnancy Complications, Cardiovascular; Pregnancy Outcome; Pregnancy, High-Risk